Contribution to the study of soil stabilized by ballast columns - Bencheikh Boutahir Born, Messaouda; Aidoud, Assia; Benamara, Fatima Zohra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Ballasted columns are an interesting technique for improving compressible soils in situ. Their major advantages are to reduce compaction, increase the bearing capacity of soils, accelerate consolidation, and eliminate the risks of liquefaction during earthquakes. Thanks to these advantages, reinforcement processes are considerably developed in the field of geotechnical construction and this is on an international scale.
Keywords: ballast columns; compressible soils; study of soils; soil stabilizer; in situ; słupy balastowe; grunty ściśliwe; badania gruntów; stabilizowanie gruntów